Efecto de Trichoderma spp. sobre Fusarium oxysporum aislado de Musa acuminata variedad Gros Michel procedente de la localidad de Molino Cajanleque, La Libertad. - Vela Novoa, José Antonio (2019)
Trichoderma is one of the main biological agents in the management of Panama disease. The objective of this study was to determine the effect of Trichoderma spp. on Fusarium oxysporum isolated from Musa acuminata (Gros Michel) from Molino Cajanleque, La Libertad. It was worked with T. harzianum, T. viride and Trichoderma sp. Each species of Trichoderma was confronted with F. oxysporum using the dual culture technique to select the best antagonist and continue to evaluate the filtrate on the growth and germination of F. oxysporum. The species T. harzianum and T. viride presented class II antagonism, while Trichoderma sp. presented antagonism class I, also the highest percentage of inhibition of radial growth. Trichoderma sp. produced deformation and fragmentation of the mycelial structure of F. oxysporum, having a destructive effect. The filtrate of Trichoderma sp. decreased the growth of F. oxysporum by 25% and inhibited germination at 100%, observing morphological alterations in conidia. In conclusion, it was evidenced that the three species of Trichoderma are antagonists to F. oxysporum in varying degrees, being Trichoderma sp., the antagonist with the best inhibitory effect.